Anthropolinguistic Mythological Study of Hamlet Names in Wonosari Distric - Veramita Umar; Karim Baruadi; La Ode Gusman Nasiru (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The object of this research is the names of hamlets in Wonosari District, Boalemo Regency, which are examined through a mythological and anthropolinguistic approach. This research aims to (1) describe the origins of the hamlet names; (2) describe the meaning of the hamlet names; and (3) describe the mythological elements reflected in the hamlet names. The research method used is descriptive qualitative with data collection techniques in the form of interviews, observation, note-taking, and recording. Data was obtained from community leaders, village elders, village heads, hamlet heads, and residents who knew the history and traditional stories related to the naming of hamlets. The results of the study show that of the 13 existing hamlets, only 5 have myths or origin stories that are still remembered by the community, namely Iloponu Hamlet, Olibuhu Hamlet, Oliyanuhe Hamlet, Botulontio Hamlet, and Ulintapo Hamlet. The origins of the hamlet names are generally related to natural elements, past events, and community beliefs, such as the existence of springs, certain trees, traditional fire-making techniques, and places considered sacred. Mythological analysis using the concept of Levi-Strauss’s mythome reveals that these natural elements become units of meaning that form the structure of the story and reflect the way of life of the Pangeya community, meanwhile, anthropolinguistic analysis shows that the naming of hamlets not only functions as a geographical identity, but also as a symbolic form that records cultural values, collective memory and the harmonious relationship between humans and nature. Based on the research results, it can be concluded that the names of the hamlets in Pangeya Village contain profound cultural meaning, particularly related to local wisdom passed down through oral tradition. This research is expected to contribute to the development of anthropolinguistic studies, local mythology, and efforts to preserve regional culture in Gorontalo.